Viability of Neotyphodium endophytic fungus and endophyte-infected and noninfected Lolium multiflorum seeds - Gundel, Pedro E. (2009)
Fil: Gundel, Pedro E. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas vinculadas a la Agricultura; Argentina.